Traditional conflicts and dynamic coalitions at the World Climate Conference: COP28: new room for manœuvre in international climate politics - Jule Könneke; Ole Adolphsen (Stiftung Wissenschaft und Politik (SWP), 2024)
The outcome of the 28th UN Climate Change Conference shows that international cooperation remains possible despite today's challenging geopolitical situation. Instead of the feared blockade, an agreement was reached for the first time - some three decades after the start of the COP process - to move away from fossil fuels in energy systems. Overall, the steps agreed in Dubai are a compromise that sends a political signal short of what is necessary from a scientific perspective. On the one hand, international climate cooperation continues to be characterized by traditional conflicts between developing countries and industrialized nations (issues of global justice, financial commitments), with new trade tensions and what at times amounted to an obstructionist attitude among a handful of countries compounding the difficulties. On the other hand, dynamic North-South coalitions have formed in the negotiation tracks on 'loss and damage' and the global energy transition. These must be further strengthened as the starting point for lasting alliances against fossil fuel interests. German climate foreign policy can make an important contribution by undertaking consistent diplomatic efforts to implement structural reforms of the international financial system and by offering attractive partnerships.
Keywords: 320; World Climate Conference; COP28; Global North; Global South; Russia's war of aggression against Ukraine; energy security; Global Stocktake (GST); nationally determined contributions (NDCs); carbon border adjustment mechanism (CBAM); Intergovernmental Panel on Climate Change (IPCC)